Acid-Catalyzed Tandem Process for the One-Pot Synthesis of Oxazolidines - Aldmairi, Abdul Hadi; Knight, David W.; Wirth, Thomas (Synlett, 2017)
A simple protocol for the synthesis of oxazolidines from aziridines and allylic alcohols is reported. The solid-supported sulfonic acid catalyst can be easily removed after the reaction by a simple filtration leading to the oxazolidine reaction products in good to excellent yields.
Keywords: aziridines; cyclization; oxazolidines; rearrangement; ring opening